Proses Pembayaran Uang Japuik Dan Uang Ilang Dalam Sistem Perkawinan Di Nagari Manggopoh Kabupaten Agam - Susi Delmiati (IJOCE: Indonesia Journal of Civic Education, 2020)
The purpose of this study was to determine the process of paying japuik and moneylang money in the marriage system in Nagari Manggopoh, Agam Regency. This type of research is a qualitative research with a descriptive type. The research informants were determined by purposive sampling. The results of this study indicate that the process of paying japuik money includes: a) Determination of the nominal value of japuik money by both parties during maresek / maanta asok, b) Determination of the time of payment of japuik money, which is when picking up The bride and groom at night after the beretong event, c) The female mother hands over the japuik money to the male mamak. Meanwhile, the process of paying lost money includes: a) Determination of the nominal value of lost money by both parties during maresek / maanta asok, b) Determination of the time for payment of lost money, namely before the wedding party, c) Handover money lost between the parents of both parties, namely before the wedding party. The conclusion is that there are similarities and differences in the process of determining japuik money and money lost, namely both determining the nominal money, the difference in the timing of funding before and during the wedding, and the difference in the handover. Keywords: Jengik money and lost money